Synthesis and Characterization of New Schiff Bases Derivative from 2, 5ـ Dimarcaptothiadiazole - Israa Taha Ibraheem (Journal of Global Pharma Technology, 2016)
This research includes synthesis of new heterocyclic containing Schiff bases derivatives of 2, 5ـdimarcapto thiadiazole. The preparation process started by the reaction of 2,5ـdimercaptoـ1,3,4ـthiadiazole (1) with ethyl chloroacetate to give diethyl 2,2`-(1,3,4-thiadiazole-2,5-diyl)bis(sulfanediyl)diacetate (2). Compound (1) reacted with hydrazine hydrate to give 2, 5ـbis (mercaptoـacetichydrazide) 1, 3, 4ـthiadiazole (3). The reacted with various substituted benzaldehydes in the presence of glacial acetic acid as catalyst in absolute ethanol to obtain new Schiff bases derivatives (4-13).Keywords: 2, 5ـ dimercaptoـ1, 3, 4ـthiadiazole, Schiff bases.